(untitled) (Fractal: Journal of Psychology, 2013)
We have investigated aspects such as the use of objects and the possibility of change in these children on the autistic spectrum in speech therapy of Interactionism conception. The subjects were three children diagnosed with Pervasive Development Disorder, their mothers and speech therapist. Children were videotaped during free play to the first and tenth month of therapy. There have been changes in play and use the object in the subjects. It is the effectiveness of the promotion of play therapy as well as the knowledge and observation of the object types and object relationship is an important clinical indicator.